Pan-immune-inflammation value and prognostic nutritional index can predict the 2-year recurrence of triple-negative breast cancer patients after radical resection - Xia, Zhenhua; Dai, Yuping; Zhang, Jun; Yang, Liguo; Yang, Zhigang (Frontiers in Oncology, 2026)
ObjectiveThis study investigates the value of Pan-Immune-Inflammatory Value (PIV) and Prognostic Nutritional Index (PNI) in predicting the recurrence of triple-negative breast cancer (TNBC) patients within 2 years after radical surgery.MethodsThis study retrospectively selected the medical records of 130 TNBC patients who underwent radical surgery at Shidong Hospital of Yangpu District in Shanghai from January 2020 to March 2023. The preoperative PIV and PNI values and clinical data of the patients were collected, and the patients were divided into a recurrence group (47 cases) and a non-recurrence group (83 cases) based on the follow-up results within 2 years after surgery. The optimal cutoff values of PIV and PNI were determined through receiver operating characteristic (ROC) curves, and their predictive values for recurrence within 2 years after surgery were analyzed. Binary logistic regression models were used to analyze the independent predictive effects of PIV and PNI on recurrence within 2 years after surgery, and nomogram models were constructed to evaluate their clinical application value.ResultsTumor diameter (OR: 1.754, 95% CI: 1.156–2.663), SII (OR: 1.560, 95% CI: 1.053–2.312), PIV (OR: 1.891, 95% CI: 1.217–2.938), and PNI (OR: 0.676, 95% CI: 0.473–0.966) are factors affecting recurrence within 2 years after surgery in TNBC patients. Multivariate Cox regression analysis showed that low PNI (HR = 2.25, 95% CI: 1.40–3.62, P = 0.001) and high PIV (HR = 1.83, 95% CI: 1.17–2.86, P = 0.008) are independent risk factors for tumor recurrence within 2 years after surgery in TNBC patients. Patients with high PIV and low PNI (n=28) had the poorest RFS, while those with low PIV and high PNI (n=35) had the best outcomes. The calibration curve of the nomogram model constructed based on PIV and PNI showed a high consistency between the predicted and actual values.ConclusionPIV and PNI can serve as effective indicators for predicting recurrence within 2 years after radical surgery in TNBC patients, providing a more scientific reference for clinicians.